MEMBANGUN PEMAHAMAN TERHADAP KARYA SASTRA BERBENTUK FIKSI (TELAAH SIFAT DAN RAGAM FIKSI NARATIF) - Siti Musyarofah (HUMANIS: Jurnal Ilmu-Ilmu Sosial dan Humaniora, 2020)
Some people who appreciate literature still discuss about the real of each terms which often appear in literary works especially in narrative fiction, such as plot, story, character, characterization, and conflict. Eventhough, there are some people who appreciate literature who are not able to differentiate those terms. That is why, the purpose of this article is to explain the position of literary works in fiction, especially narrative fiction. Because of characteristic of fiction include all the aspects of story so in this article explain about story, plot, and conflict. Story as an even which followed by other even, then followed by another even, and so on, while plot as even series which is composed by cause and effect. Meanwhile, conflict is created by the interaction of each character. Without interaction, a conflict could not be created. So that is why, a conflict as a part of integral that should be stated in. Good or bad o a conflict depend on the criteria of conflict itself.